Penerapan teori behavioristik skinner dalam pembelajaran matematika - Afriska Della Imamiyah; Nur Laella Romadhoni; Amelia Syah Fitrih; Kharisma Putri Erlinawati; Mohammad Nurwahid (Journal of Profession Education, 2024)
Mathematics learning is often perceived as difficult by students due to its abstract nature and the procedural skills required to solve problems. One approach that can support the learning process is behaviorist learning theory, which emphasizes the stimulus–response relationship and the role of reinforcement in shaping learning behavior. This study aims to analyze the implementation of B. F. Skinner’s behaviorist learning theory in mathematics learning. The research employed a qualitative approach using a library research method. Data were collected through a systematic search of relevant literature, including journal articles, conference proceedings, and books. A total of 20 sources published between 2013 and 2023 were selected based on predetermined inclusion criteria. The data were analyzed using content analysis to identify key concepts and patterns in the application of behaviorist theory in mathematics learning. The results indicate that behaviorist principles can be implemented through drill and practice, reinforcement, structured learning activities, and immediate student feedback. These strategies help improve students’ motivation to learn, accuracy in solving mathematical problems, and understanding of mathematical concepts.